SISTEM PAKAR DIAGNOSA PENYAKIT GINJAL PADA ANAK MENGGUNAKAN METODE ANALIYTICAL HIERARCHY PROCESS (AHP) DAN CERTAINTY FACTOR - Saputra, Lucky; Martinus, Agust Isa; Gunawan, Harry (Program Studi Teknik Informatika Universitas Muhammadiyah Cirebon, 2025)
The rise of kidney disease cases in children has become a serious concern in the health sector. Lack of information related to kidney disease in children can lead to the worsening of the child's illness which can lead to more serious complications. To overcome this problem, the development of an expert system for diagnosing kidney disease in children is an important solution. This expert system is built using the Analytical Hierarchy Process (AHP) method as a priority determinant (weight) with pairwise comparisons of symptoms in existing diseases and Certainty Factor to calculate the percentage of decision confidence with the knowledge of an expert in this system, which makes it possible to diagnose kidney disease in children. The system is web-based, ensuring easy access for users. In addition, the system also provides appropriate treatment suggestions on the disease, allowing users to take action faster. The end result of this expert system system displays diagnosis results and solutions that can help pediatric patients suffering from kidney disease. Therefore, the development of an expert system for the diagnosis of kidney disease in children has great potential to have a positive impact in the field of health, especially for children. Keywords: Expert system, Diagnosis, Pediatric Kidney Disease, Analytical Hierarchy Process (AHP), Certainty Factor